The Connection of peak alarm rates to plant incidents and what you can do to minimize. Issue 1 (27th November 2012) - Beebe, Dustin; Ferrer, Steve; Logerot, Darwin
<x xml:space="preserve">Abstract</x> Even after several years of trying, many plants still struggle with controlling alarm floods. Static rationalization can reduce your average number of alarms but without controlling the alarm floods, there is no help for the operator when he needs it the most. This session will cover the justification for alarm management from the safety and environmental as well as economic perspective. © 2012 American Institute of Chemical Engineers Process Saf Prog 32: 72–77, 2013